Legal basis for pt mitsubishi company's consideration in resolving employee grievances of labor union members - Lubis, Adrylan; Hifni, Mohammad (Journal of Law Science, 2024)
PT Mitsubishi's Corporate Rationale for Resolving Employee Grievances of Trade Union Members is an important guideline in building harmonious and conducive working relationships. This paper outlines the principles and guidelines for company management and Trade Union officials in handling employee grievances in a fair, transparent and accountable manner. The purpose of this research is to try to provide solutions to employee union members to answer the unrest experienced by PT Mitsubishi employees. The research method in this study uses descriptive qualitative research methods using survey and interview methods. The conclusion of this study is to answer all complaints from employees of PT Mitsubishi union members.